A novel wide temperature range and multi-mode optical thermometer based on bi-functional nanocrystal-doped glass ceramics. Issue 37 (4th September 2018) - Cai, Zhenlu; Kang, Shiliang; Huang, Xiongjiang; Song, Xiaoqian; Xiao, Xiudi; Qiu, Jianrong; Dong, Guoping
Abstract : A multi-mode optical thermometer was developed using novel nanocomposite glass ceramics, containing bi-functional NaYF4 :Yb 3+ /Nd 3+ and NaAlSiO4 :Cr 3+ nanocrystals. Abstract : Novel nanocomposite glass ceramics (GCs), containing bi-functional NaYF4 :Yb 3+ /RE 3+ (RE 3+ = Er 3+, Nd 3+ ) and NaAlSiO4 :Cr 3+ nanocrystals, were synthesized by a melt-quenching process and subsequent heat-treatment. XRD and TEM results indicate that two types of nanocrystals, NaYF4 and NaAlSiO4, disperse homogeneously in the glass matrix. Photoluminescence (PL) spectra and lifetime measurements demonstrate that RE 3+ and Cr 3+ ions selectively enter into the precipitated NaYF4 and NaAlSiO4 nanocrystals, respectively, after crystallization, which restrains the potential energy transfer (ET) between the rare earth (RE) and transition metal (TM) ions. Significantly, there are three modes to carry out the optical thermometry based on the fluorescence intensity ratio (FIR) from two thermally coupled levels of Nd 3+, the FIR from the Cr–Nd non-thermally coupled system and the fluorescence lifetime of Cr 3+ . Compared to standard temperature sensors based on a single mode technique, the Yb 3+ /Nd 3+ /Cr 3+ codoped oxyfluoride GCs, with excellent sensitivity and high precision, open up a new path in the optical thermometry field.